Does Education Raise Productivity and Wages Equally? The Moderating Roles of Age, Gender and Industry - Francois Rycx; Yves Saks; Ilan Tojerow (Institute for the Study of Labor (IZA), 2015)
The labour market situation of low-educated people is particularly critical in most advanced economies, especially among youngsters and women. Policies aiming to increase their employability either try to foster their productivity and/or to decrease their wage cost. Yet, the evidence on the misalignment between education-induced productivity gains and corresponding wage cost differentials is surprisingly thin, inconclusive and subject to various econometric biases. We estimate the impact of education on productivity, wage costs and productivity-wage gaps (i.e. profits) using rich Belgian linked employer-employee panel data. Findings, based on the generalised method of moments (GMM) and Levinsohn and Petrin (2003) estimators, show a significant upward-sloping profile between education and wage costs, on the one hand, and education and productivity, on the other. They also systematically highlight that educational credentials have a stronger impact on productivity than on wage costs. This 'wage compression effect', robust across industries, is found to disappear among older cohorts of workers and to be more pronounced among women than men. Overall, findings suggest that particular attention should be devoted to the productivity to wage cost ratio of low-educated workers, especially when they are young and female, but also to policies favouring gender equality in terms of remuneration and career advancement.
Keywords: C33; I21; J24; J31; 330; education; labour costs; productivity; linked panel data